Case Report: Expanding the Digenic Variants Involved in Thyroid Hormone Synthesis−10 New Cases of Congenital Hypothyroidism and a Literature Review - Yang, Rulai; Lu, Yijun; Yang, Chenxi; Wu, Xiaoyu; Feng, Junqi; Zhu, Ling; Shu, Qiang; Jiang, Pingping (Frontiers in Genetics, 2021)
Congenital hypothyroidism (CH) is the most common neonatal metabolic disorder. Although it has been understood to be monogenic disease, some CH patients are reported to carry two or more variants at different genes. Here, ten permanent congenital hypothyroidism (PCH) patients were retrospective, with elevated levels of serum thyroid stimulating hormone and levothyroxine–dependent during follow-up between 2015 and 2019. Each affected individual carried digenic loci which was heterozygous at two of pathogenic genes. Total 5 pathogenic genes, TSHR, TG, TPO, DUOX2 and DUOXA2, were simultaneously identified in subjects that involved in the same metabolic pathway- thyroid hormone biosynthesis. There were digenic loci at TSHR and DUOX2 combined in 3 patients, DUOX2 and TG combined in 2 patients, DUOX2 and DUOXA2 combined in 2 patients, TG and DUOXA2 combined in 2 patients, and TG and TPO combined in one patient. Additionally, seven novel variants, TSHR c.679G>A, DUOX2 c.127A>T, c.608-619del and c.959T>C, TG c.2307G>A and c.6759_6765del; and DUOXA2 c.93T>G, were identified in these PCH patients. Our findings could contribute to the existing knowledge on clinical and genetic diagnosis of patients with CH.